Are oral health conditions associated with schoolchildren's performance and school attendance in the Kingdom of Bahrain? A life‐course perspective. Issue 2 (13th June 2021) - Mohamed, Seham A. S.; Baker, Sarah R.; Deery, Christopher; Vettore, Mario V.
Abstract: Background: The link between oral diseases and school performance and school attendance remains unclear among Middle Eastern children. Aim: To investigate the relationship of oral conditions with schoolchildren's school performance and attendance using the life‐course approach. Design: A cross‐sectional study was conducted with 466 schoolchildren aged 7‐8 years from Kingdom of Bahrain (KoB) and their parents. Questionnaire data on children's current and at‐birth environmental characteristics were completed by their parents. Children's oral health measures, including ICDAS (International Caries Detection and Assessment System), PUFA (pulp, ulcer, fistula, abscess), and DDE (developmental defects of enamel) indices, were the exposure variables. School performance and school attendance data obtained from the school register were the outcome variables. The data were analysed using multivariate ordinal logistic regression. Results: The odds of excellent school performance were significantly lower for children with untreated dentinal caries (OR = 0.98; 95% CI: 0.96‐0.99). Children with caries‐treated teeth showed greater odds of excellent school performance (OR = 1.41; 95% CI: 1.15‐1.74). Disease Control and PreventionNone of the dental conditions were significantly associated with children's school attendance. A permissive parental style was associated with poor school attendance (OR = 2.63; 95% CI: 1.08‐6.42). Conclusion: Dental caries was associated with poor school performance but not with school attendance. Treated caries was associated with good school performance.